DIGITALISASI SISTEM INFORMASI MANAJEMEN MASJID MODERN - Sutono; Ai Musrifah; Repi Maulana Risyan (Universitas Majalengka, 2023)
The mosque is one of the important elements in the structure of the life of Islamic society. The mosque is a place for religious activities of the Islamic community. Mosque management tends to focus on managing its congregation with congregational service orientation. The purpose of making this system is to provide optimal service to the congregation so that they can be comfortable in carrying out all religious activities that can be carried out at the mosque, so that through technology the manager can also overcome the problems encountered in the process of routine mosque activities. This research will design the digitization of a mosque's management information system with an object-oriented model based on the Waterfall method. The digitization of this modern mosque management information system is able to provide satisfaction to system users and considers that the existence of a system for managing mosque operational activities is considered important. abstrak Masjid merupakan salah satu elemen penting dalam struktur kehidupan masyarakat Islam. Masjid merupakan tempat kegiatan keagamaan umat Islam. Pengurus masjid cenderung fokus pada pengelolaan jemaahnya dengan orientasi pelayanan berjamaah. Tujuan dibuatnya sistem ini adalah untuk memberikan pelayanan yang optimal kepada jamaah agar dapat nyaman dalam menjalankan segala aktivitas keagamaan yang dapat dilakukan di masjid, sehingga melalui teknologi pengelola juga dapat mengatasi permasalahan yang dihadapi dalam prosesnya. kegiatan rutin masjid. Penelitian ini akan merancang digitalisasi sistem informasi manajemen masjid dengan model berorientasi objek berdasarkan metode Waterfall. Digitalisasi sistem informasi manajemen masjid modern ini mampu memberikan kepuasan bagi pengguna sistem dan menganggap keberadaan sistem pengelolaan kegiatan operasional masjid dianggap penting.